Implementing Comprehensive Literacy Instruction for Students With Severe Disabilities in General Education Classrooms. (April 2020) - Hunt, Pam; Kozleski, Elizabeth; Lee, Jaehoon; Mortier, Kathleen; Fleming, Danielle; Hicks, Tyler; Balasubramanian, Lakshmi; Leu, Grace; Bross, Leslie Ann; Munandar, Vidya; Dunlap, Kristin; Stepaniuk, Inna; et al.
The purpose of this conceptual replication study was to investigate the efficacy of an early literacy intervention when it was implemented by special educators in general education classrooms with students in the class participating in the lessons. The study was conducted in 16 schools in three states. Eighty students with severe disabilities participated in the study. Students in the intervention group received Early Literacy Skills Builder (ELSB) instruction, and students in the "business-as-usual" control group received literacy instruction planned by special education teachers to address the students' individualized education program literacy goals. Literacy assessments were conducted in five waves scheduled across the school year. Results showed that students receiving ELSB instruction made greater gains in assessed literacy skills than students in the control group. These findings provide evidence that students with severe disabilities can benefit from comprehensive emergent literacy instruction when it is implemented in general education settings.